AUTOMATED DETERMINATION OF THE CRYSTALS SIZE IN ELECTRODEPOSITED METAL MATERIALS - E. V. Kolesnik (Литьë и металлургия)
Methods of automated determination of the crystals size in the electrodeposited metal materials including digital processing of the electronicand microscopic image of the structure with sequential use of the low-and-high-leaky filter based on fast transformation of Fourier, Watershed-algorithm and decomposing of Voronoj with further measurement of thr crystal size with one of the traditional methods is offered.